Selected Lectures of the National Congress of the Italian Society of Pediatric Psychology (S.I.P.Ped.); Cagliari (Italy); October 20, 2023 - Various Authors, — (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2023)
Selected Lectures of the National Congress of the Italian Society of Pediatric Psychology (S.I.P.Ped.); Cagliari (Italy); October 20, 2023 The National Congress of the Italian Society of Pediatric Psychology (Società Italiana di Psicologia Pediatrica – S.I.P.Ped.) is a Satellite Meeting of the 19th International Workshop on Neonatology and Pediatrics, Cagliari (Italy), October 18th-21st, 2023. LECT 1. HOW TO RECOGNIZE AND COPE WITH POSTPARTUM DEPRESSION. PEDIATRICIAN AND PSYCHIATRIST’S ANSWERS TO PARENTS’ QUESTIONS • V. Fanos, T. Fanos, M. Corridori (Cagliari, Mantua and Verona, and Quartu Sant’Elena, Italy) LECT 2. FAMILY PEDIATRICS, PREVENTIVE AND SOCIAL PEDIATRICS, AND PEDIATRIC PSYCHOLOGY • G. Di Mauro (Caserta, Italy) LECT 3. INTEGRATED WORK IN PEDIATRIC PSYCHOLOGY • G. Perricone (Palermo, Italy) LECT 4. THE EXPERIENCE IN PEDIATRIC ONCOHEMATOLOGY • M. Jankovic (Monza, Italy) LECT 5. WHEN CHRONICITY BEATS WITH A “DIFFERENT HEART” IN PREGNANCY • F. De Luca (Catania, Italy) LECT 6. MATERNAL ARCHETYPE AND POSTPARTUM DEPRESSION. A NEURO-NARRATIVE COMMUNICATION PERSPECTIVE • M. Zonza (Carbonia, Italy) LECT 7. EFFECTS OF MATERNAL PERINATAL DEPRESSION ON INFANT TEMPERAMENT AND FEEDING INTERACTIONS IN THE FIRST 6 MONTHS OF LIFE • L. Lucarelli, C. Sechi, L. Vismara (Cagliari, Italy) LECT 8. KNOWING PEDIATRIC HEADACHES • M. Carotenuto (Naples, Italy) LECT 9. PEDIATRICIANS AND PSYCHOLOGISTS IN THE MANAGEMENT OF CHILD NEGLECT ASSESSMENT • C. Polizzi and S.I.P.Ped. Research Group: “A Dysregulation of Parenting Competence: Neglect” (Palermo, Italy) LECT 10. PSYCHOLOGY, CHILDREN, NUTRITION • S. Petza (Cagliari, Italy)